Two dimensional grating and efficiency enhancement of Si photovoltaic cells by surface texturing using UV femtosecond laser pulses - Al-Naimee, K. (Iraqi Journal of Physics, 2011)
A fast laser texturing technique has been utilized to produce micro/nano surface textures in Silicon by means of UV femtosecond laser. We have prepared good absorber surface for photovoltaic cells. The textured Silicon surface absorbs the incident light greater than the non-textured surface. The results show a photovoltaic current increase about 21.3% for photovoltaic cell with two-dimensional pattern as compared to the same cell without texturing.